Nurse role and mechanism of Coriaria nepalensis in abandoned land of Pb-Zn mining area - Yang, Jie; Tang, Hong; Duan, Chang-qun; Wang, Si-chen; Yuan, Xin-qi; Huang, Lv; Li, Lin-yang (Frontiers in Ecology and Evolution, 2023)
Mining activities, while providing a huge material base for human society, have also caused great damage to the ecosystem. A large amount of mine waste is in urgent need of treatment and remediation. Phytoremediation, as a green and low-cost way of mine site restoration, has been researched by a large number of scholars. Ecological restoration, as a suitable alternative to phytoremediation, has also received extensive attention from scholars too. Field survey revealed that a native plant, Coriaria nepalensis, adapted to the abandoned sites of Pb-Zn mines for its adaptability to pollution and extreme habitats and its improvement of the surrounding microenvironment, with its formation of plant communities may contribute to the natural recovery of the abandoned sites of mines. For this reason, the present study was conducted on the nurse plant, C. nepalensis, which was naturally colonized in the abandoned land of the Pb-Zn mine in Mine Town, Huize County. The specific results of the study are as follows: C. nepalensis can have a nurse effect on its sub-canopy plants by improving microhabitat soil properties and regulating soil microbial community structure in abandoned sites of Pb-Zn mines, thus enabling plant community succession in degraded environments.